INTEREST RATES CHARGED ON INSTALLMENT PURCHASES. - Botts, Ralph R.; Garlock, Fred L. (The Accounting Review, 1955)
Retail selling on the installment plan is a widely accepted practice. Yet few buyers know the interest-rate equivalent of the carrying charges they pay for installment credit. That it is usually relatively high no one denies. This situation has led to suggestions from some quarters that sellers be required to specify on theft sales contracts the interest-rate equivalent of their service charges, so that buyers will be better able to determine whether they are paying "too much" for the privilege of using installment credit. Perhaps one reason why state laws have not required the posting of equivalent annual interest rates is that several methods of computing rates are in use and all are apparently recognized as valid. This creates a confusing situation. This article reviews some of the more commonly used methods of computing equivalent rates and tries to determine whether certain of them should be favored over others. Eight methods of computing the rate equivalent of the service charge in the illustrative problem may be considered. However, relatively few consumers know how to apply even the simplest of these methods, and several of the methods do not provide an accurate measure of the differences between rates. Any method recommended for general use, including use by sellers, should be accurate and as easy as possible to compute.